2018
DOI: 10.4274/balkanmedj.2018.0083
|View full text |Cite
|
Sign up to set email alerts
|

Current Practice in Obstetric Anesthesia and Analgesia in Public Hospitals of Greece: A 2016 National Survey

Abstract: Aims:This descriptive survey was to evaluate the use of regional anesthesia in obstetrics in Greek public hospitals.Methods:The survey was conducted between March and August 2016. A structured questionnaire was sent to 50 anesthesia departments in Greek public hospitals with obstetric units.Results:The response rate was 94%. Data corresponding to 9475 cesarean and 8155 vaginal deliveries were collected. Regional anesthesia was used in 69.2% of all cesareans, with single shot spinal being the most popular (44.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
1
9
0
1
Order By: Relevance
“…At present, the cesarean section rates in developed countries are 10%-20% and the labor analgesia rates have reached 85%-90%. [ 3 6 ] However, according to a report published in the Lancet in 2010, the cesarean section rate of puerperae with non-medical indications in China was as high as 46.2%, which ranks first in the world and triples the upper limit of the World Health Organization standard (15%). [ 7 ] Moreover, in some regions, this rate can reach up to 70%, whereas the overall analgesia rate of puerperae is less than 5%.…”
mentioning
confidence: 99%
“…At present, the cesarean section rates in developed countries are 10%-20% and the labor analgesia rates have reached 85%-90%. [ 3 6 ] However, according to a report published in the Lancet in 2010, the cesarean section rate of puerperae with non-medical indications in China was as high as 46.2%, which ranks first in the world and triples the upper limit of the World Health Organization standard (15%). [ 7 ] Moreover, in some regions, this rate can reach up to 70%, whereas the overall analgesia rate of puerperae is less than 5%.…”
mentioning
confidence: 99%
“…Staikou et al reported that anesthetists in Greece prefer general anesthesia for the refugees and asylum-seekers living in rural areas, and did not prefer regional anesthesia due to language and religious barriers. [22] However, Yazar et al performed a questionnaire study on Turkish anesthesiologists, which investigate the preference for perioperative anesthesia methods on refugee and asylum-seeker patients, and they reported that 31% of the anesthesiologists prefer general anesthesia rather than regional anesthesia. [23] When the anesthesia methods applied in this study considered, the rates of use of general anesthesia and spinal anesthesia were similar.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that single-shot spinal anesthesia was preferred in cesarean sections, and epidural analgesia is rarely used in normal spontaneous vaginal delivery in all clinics, especially in peripheral hospitals. Writers have emphasized that the epidural labor analgesia is not widely recognized and should be utilized more frequently in clinical practice [25]. Although the labor analgesia is technically quite easy, the most important difficulty seems to be that application is not becoming widespread.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Sahin S et al reflects the facts of our country. Low recognition and low rates of utilization of labor analgesia in clinical practice may cause an increase in caesarean section frequency [1,25]. Many studies use VAS in assessing pain.…”
Section: Discussionmentioning
confidence: 99%